2007
DOI: 10.1158/1055-9965.epi-06-0121
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Akt (Ser473) Predicts Poor Clinical Outcome in Oropharyngeal Squamous Cell Cancer

Abstract: Background: Several lines of laboratory evidence support a role of persistent activation of Akt pathway in oropharyngeal squamous cell carcinoma (OSCC) progression. Loss of phosphatase PTEN is one of the proposed mechanisms of Akt activation. We sought to determine the prognostic significance of Akt activation in a cohort of patients with OSCC as well as the association between phosphorylated (activated) Akt and PTEN levels. Methods: Using a novel system of in situ quantitative protein expression analysis (AQU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 25 publications
3
45
0
1
Order By: Relevance
“…Either of these mechanisms can lead to rebound enhancement of AKT function and induce a recovery of prosurvival signals (Figure 10). High AKT activity is associated with a poor prognosis as well as resistance to chemotherapy (35,36).…”
Section: Figurementioning
confidence: 99%
“…Either of these mechanisms can lead to rebound enhancement of AKT function and induce a recovery of prosurvival signals (Figure 10). High AKT activity is associated with a poor prognosis as well as resistance to chemotherapy (35,36).…”
Section: Figurementioning
confidence: 99%
“…Interestingly, TGF-b polymorphisms have been reported to be a susceptibility marker for HPV16 status amongst patients with OPC (35). Furthermore, the miR106b-25 cluster can also target PTEN (20), which in turn will activate AKT, which correlates with adverse outcome for patients with OPC (36). Hence, dysregulation of MCM7 and the miR-106b-25 cluster could lead to OPC development via aberrant TGF-b and PTEN signaling (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Massarelli et al reported that tongue cancer patients with Ki67 expression showed significantly shorter disease-free survival [8]. Yu et al reported that OPSCC patients with a low Ki67 level had a lower 5-year local recurrence rate and better 5-year overall survival rate [9].…”
Section: Discussionmentioning
confidence: 99%